2021
DOI: 10.1155/2021/4665632
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Protective Effect of Nicorandil on Cardiac Microvascular Injury: Role of Mitochondrial Integrity

Abstract: A major shortcoming of postischemic therapy for myocardial infarction is the no-reflow phenomenon due to impaired cardiac microvascular function including microcirculatory barrier function, loss of endothelial activity, local inflammatory cell accumulation, and increased oxidative stress. Consequently, inadequate reperfusion of the microcirculation causes secondary ischemia, aggravating the myocardial reperfusion injury. ATP-sensitive potassium ion (KATP) channels regulate the coronary blood flow and protect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 126 publications
0
11
0
1
Order By: Relevance
“…Likewise, the antioxidant activity of melatonin in reducing the adverse effects of I/R injury was also shown to be related to its inhibitory action on the mitochondrial permeability transition pore opening as well as up-regulation of cytochrome c oxidase activity [ 127 , 128 ]. In addition, nicorandil, a mitochondrial ATP-sensitive potassium channel opener, has been demonstrated to prevent I/R-induced injury to the myocardium, alleviate cardiomyocyte necrosis, attenuate endothelial dysfunction, and improve blood flow as well as cardiac function [ 129 ]. These experimental observations indicate that several cardiac alterations induced by I/R injury are prevented by treatment with a wide variety of pharmacological agents including antioxidants; however, extensive research work needs to be carried out to establish if these interventions are able to reverse the I/R-induced myocardial abnormalities.…”
Section: Pharmacotherapy Of I/r Injury To the Heartmentioning
confidence: 99%
“…Likewise, the antioxidant activity of melatonin in reducing the adverse effects of I/R injury was also shown to be related to its inhibitory action on the mitochondrial permeability transition pore opening as well as up-regulation of cytochrome c oxidase activity [ 127 , 128 ]. In addition, nicorandil, a mitochondrial ATP-sensitive potassium channel opener, has been demonstrated to prevent I/R-induced injury to the myocardium, alleviate cardiomyocyte necrosis, attenuate endothelial dysfunction, and improve blood flow as well as cardiac function [ 129 ]. These experimental observations indicate that several cardiac alterations induced by I/R injury are prevented by treatment with a wide variety of pharmacological agents including antioxidants; however, extensive research work needs to be carried out to establish if these interventions are able to reverse the I/R-induced myocardial abnormalities.…”
Section: Pharmacotherapy Of I/r Injury To the Heartmentioning
confidence: 99%
“… 29 The release of both pro-inflammatory mediators, such as TNF-α and IL-1β, and ROS plays an important role in the development and progression of MNR. 30 We found that nicorandil could improve inflammation and oxidative stress, which may participate in MNR, in addition to its effect on vasodilation in this trail. Thus, the suppression of MNR by nicorandil might occur through the inflammatory pathway.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, nicorandil dilates the microvasculature to improve cardiac perfusion by activating potassium ATP channels ( 19 ). Nicorandil also protects cardiomyocytes by opening the mitochondrial potassium ATP channels in ischemia-reperfusion conditions ( 20 ). In patients with ST-segment elevation myocardial infarction, intracoronary or intravenous administration of nicorandil during primary PCI improved myocardial microcirculation and reduced infarct size ( 21 23 ).…”
Section: Discussionmentioning
confidence: 99%